1991
DOI: 10.1111/j.1528-1157.1991.tb04684.x
|View full text |Cite
|
Sign up to set email alerts
|

Seizures in Series: Similarities Between Seizures of the West and Lennox‐Gastaut Syndromes

Abstract: We observed seizures resembling infantile spasms in patients with Lennox-Gastaut syndrome (LGS). Infantile spasms, the type of seizures that occurs in patients who have West syndrome, have been well characterized by video-EEG studies and typically occur as a series of sudden generalized flexor or extensor jerks. The seizure types that occur in LGS have not been as clearly delineated. Some patients with West syndrome (WS) in early infancy later develop LGS. Using intensive video-EEG monitoring, we evaluated 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 22 publications
2
33
0
Order By: Relevance
“…Boys are affected more frequently than girls (5,9). In this study, 15% of the patients were diagnosed as LGS at the age of 1-3 years, 40% were diagnosed at the age of 3-5 years and 45% were diagnosed at the age of 5-8 years.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…Boys are affected more frequently than girls (5,9). In this study, 15% of the patients were diagnosed as LGS at the age of 1-3 years, 40% were diagnosed at the age of 3-5 years and 45% were diagnosed at the age of 5-8 years.…”
Section: Discussionmentioning
confidence: 50%
“…Neuromotor development is affected more severely (5). While the risk of development of Lennox-Gastaut syndrome is lower in patients with West syndrome who are given ketogenic diet, prednisolone and ACTH, it has been reported that no relation was found between the age at the time of diagnosis of West syndrome and the etiology (12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The origin of hypsarrhythmia appears to be the cortical lesion as suggested by Pinard et al (13) in that a corticocortical pathway through the corpus callosum is important in the generalization of hypsarrhythmia. Repetitive tonic spasms have been observed in patients with Lennox-Gastaut syndrome (14) and periodic spasms (15), in which hypsarrhythmia was not demonstrated. We consider this additional evidence support for our proposition.…”
Section: Discussionmentioning
confidence: 99%